Object-reader, deel 1. - Dewilde, Michiel; Cultuurcentrum, Brugge (Brugge : Cultuurcentrum Brugge, 1997)
Feyzdjou, Choreh ; Lauwaert, Beatrijs ; Schärf, Uta ; Vé, Didier ; van der Pals, Anne ; de Miguel Rubio, Mónica ; Zelio, Sonja ; Fontes, Claudia
Cultuurcentrum Brugge, 1997
kunstcatalogus